2015
DOI: 10.1111/jeb.12705
|View full text |Cite
|
Sign up to set email alerts
|

A facultative endosymbiont in aphids can provide diverse ecological benefits

Abstract: Ecologically important traits of insects are often affected by facultative bacterial endosymbionts. This is best studied in the pea aphid Acyrthosiphon pisum, which is frequently infected by one or more of eight facultative symbiont species. Many of these symbiont species have been shown to provide one ecological benefit, but we have little understanding of the range of effects that a single strain can have. Here, we describe the phenotypes conferred by three strains of the recently discovered bacterium known … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
2

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(130 citation statements)
references
References 57 publications
4
124
2
Order By: Relevance
“…Based on these findings, we may expect that superinfections involving X-type plus H. defensa will be more common in warmer regions or seasons, although the loss of H. defensa-mediated resistance to parasitism at warmer temperatures (31, 33) obscures this hypothesis. Our results contrast with a previous study finding that European pea aphids superinfected with X-type and Spiroplasma showed decreased susceptibility to numerous stressors relative to those infected with Spiroplasma only (39). Given that this previous study did not isolate X-type single infections and that Spiroplamsa's only associated benefit is fungal protection (24), indirect effects may account for the enhanced protection in superinfected hosts.…”
Section: Discussioncontrasting
confidence: 56%
See 3 more Smart Citations
“…Based on these findings, we may expect that superinfections involving X-type plus H. defensa will be more common in warmer regions or seasons, although the loss of H. defensa-mediated resistance to parasitism at warmer temperatures (31, 33) obscures this hypothesis. Our results contrast with a previous study finding that European pea aphids superinfected with X-type and Spiroplasma showed decreased susceptibility to numerous stressors relative to those infected with Spiroplasma only (39). Given that this previous study did not isolate X-type single infections and that Spiroplamsa's only associated benefit is fungal protection (24), indirect effects may account for the enhanced protection in superinfected hosts.…”
Section: Discussioncontrasting
confidence: 56%
“…One common HFS, X-type, has been implicated in providing thermal tolerance and enhancing protection against parasitoid wasps and fungal pathogens (25,39). X-type is unusual among pea aphid HFS, as it occurs primarily as a superinfection with a second symbiont, H. defensa (8; this study); however, no studies have disentangled the impact of X-type on the aphid protective phenotype in single-infection and superinfection contexts.…”
Section: Discussionmentioning
confidence: 72%
See 2 more Smart Citations
“…>> Approximately here, Figure 2>> Although many microorganism-insect associations are based on nutrient and metabolite exchange, such as P-symbionts Buchnera, Blattabacterium, etc., there is evidence of the involvement of symbionts in other functions, especially those related with S-symbionts such as protection from fungal pathogens [aphids with X-type enterobacteria) (Heyworth and Ferrari 2015)] and from heat damage [aphids carrying "Candidatus Hamiltonella defensa" or "Candidatus Regionella insecticola" better tolerate high temperatures (Rusell and Moran 2006)]. Other examples of host protection from predators, pathogens and parasites include the bacterial symbiont of Paederus beetles, which produces a polyketide toxin that protects the insect larvae against predators such as the wolf spider (Kellner and Dettner 1996).…”
Section: Special Bacterial Symbiosis In Insectsmentioning
confidence: 99%